Dynamic Port-City Scapes: From Liminal "Non-Places" to Imaginative and Synergistic Adaptive Ecosystems - Höller, Lukas (author) (2020)
This research investigates the case of Kirkenes, Norway. The region with its 10.000 inhabitants is located around 400 km above the Arctic Circle within the municipality of Sør-Varanger, Finmark, and is known as the capital of the Barents Region and the gateway to the east. Located around 15km away from the Norwegian-Russian border, Kirkenes has strategic importance, being one of the main areas expected to change due to increased navigability as well as new reachability of resources benefited by a changing climate and melting Arctic sea-ice extent. The region is foreseen to become Europe’s gate and new logistic node towards the soon-to-be ice-free Northern Sea-Route, creating a 40% faster trading-route between Asia and Europe. Founded in 1905 as a harbor-town for the trans-shipment of iron ore extracted from the Sydvaranger Mine, around 8 km inland in Bjørnevatn, new port development is planned, serving as a potential strategic part for China´s “Polar Silk Road” Initiative. Despite the efforts for reinventing Kirkenes and changing its face from industrial development towards a future-proof, sustainable, and resilient Capital of the Barents Region, mining, as well as manufacturing and industrial development, never stopped being an essential factor. The municipality envisions a new and massive extra-urban port development along the neighbouring Tømmerneset Peninsula, transforming the small port into one of Scandinavia´s biggest container ports, equivalent to the current capacity of the Port of Gothenburg. The thesis focuses on the need for rethinking, adapting, and complementing current approaches on port-cities, thus spatial planning, and design as a holistic and interdisciplinary profession can gain operative power to become a mediator between the different institutional and non-institutional actors and their values to emerge a new port-city paradigm within Kirkenes. The complexity and diversity of the project-area depict the necessity to shift the perception of the port-city relationship away from a static, ...